(untitled) (Perspectivas em Ciência da Informação, 2011)
This paper presents a scheme to map competence’s attributes (knowledge, skills and attitudes) required to librarian’s work. This research and its application were made in the Central Library of the University of São Paulo, Campus of Ribeirão Preto (BCRP/USP). The attributes were identified, as well as the importance and domain of each one for BCRP/USP librarians. It was concluded that the scheme is able to provide some important references for people management in libraries.